PERIKANAN PELAGIS KECIL DI DAERAH TELUK: STUDI KASUS DI TELUK SAPE NUSA TENGGARA BARAT - Suadi Suadi (Jurnal Perikanan Universitas Gadjah Mada, 2002)
The aims of this research were to know the state of small pelagic fishery and social economic aspect of resources exploitation. To examine these issues, the research combined survey and descriptive analytic methods. Gordon-Schaefer model was applied to analyze the state of fishery and analytical descriptive to explained the relationship of the phenomena's. Data collection was based on indepth interview and recording of District Fishery Service's. Samll pelagic fisheries that been analyzed were anchovies (Stolephorus sp.), squids (Loligo sp.), and mackerels (Rastrelliger sp.).There are two main problems of fisheries in the area, firstly, the conflict on coastal zone between marine capture fisheries and mariculture. The second one is the intensive exploitation of fisheries resources. Pelagic fisheries at Sape Bay have been exploited above maximum TAC mainly 80% of MSY. MSY of anchovies (Stolephorus sp.) reached 2324,9 ton at number of effort 56534 trip and MEY 2172,3 ton at number of effort 42144 trips. MSY of squids (Loligo sp.) is 455,0 ton at number of effort 12183 trip and MEY 449,0 ton at number of effort 10780 trips equal to Bagan Perahu  trips. The model was not applicable to predict the MSY and MEY of mackerels (Rastrelliger sp.). The continuing increase of effort will depleted the stock and decreased economic rent. In addition, the increasing of competition on fishing ground with pearl culture, have resulted fishermen stress. The integrated policy and management are needed to solve these problems and to avoid social riots.